First measurement of time-dependent CP violation in Bs -> K+K- decays - collaboration, L; Aaij, R; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; et al. (2013)
Direct and mixing-induced CP-violating asymmetries in Bs -> K+K- decays are measured for the first time using a data sample of pp collisions, corresponding to an integrated luminosity of 1.0 fb^{-1}, collected with the LHCb detector at a centre-of-mass energy of 7 TeV. The results are C_{KK} = 0.14 ± 0.11 ± 0.03 and S_{KK} = 0.30 ± 0.12 ± 0.04, where the first uncertainties are statistical and the second systematic. The corresponding quantities are also determined for B0 -> pi+pi- decays to be C_{pipi} = -0.38 ± 0.15 ± 0.02 and S_{pipi} = -0.71 ± 0.13 ± 0.02, in good agreement with existing measurements.